Manajemen Need Assesment di SMP Negeri 3 Langkaplancar - Ratna Saadah Ratna Saadah; Atia Nurul Apriliani; Hilmi Fauzi; Osim Nuryana (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
This study aims to describe how the management need assessment at SMPN 3 Langkaplancar. In this study, the method used was a qualitative approach by making observations and interviews. The research subject in this study is BK Teacher who is responsible for managing guidance and counseling programs in schools. The results showed that Need Assessment Management was carried out, one of which was for the development of students' potential at SMPN 3 Langkaplancar. Various types of assessments carried out include assessment of test techniques such as conducting aptitude tests, interest tests, and achievement tests. And non-test technical assessments are carried out with various types of assessments such as DCM (Problem Checklist), AUM (General Problem Disclosure Tool), ITP (Developmental Task Inventory), ATP (Developmental Task Application), AKPD (Assessment of Student Needs). BK teachers process data to compile a program to provide services that are in accordance with student needs. BK teachers at SMPN 3 Langkaplancar said that when there are students with low assessment results, they will be given services that are in accordance with their needs, on the other hand, if students with high assessment results, BK teachers look for ways so that students can remain consistent.